Can Equity Volatility Explain the Global Loan Pricing Puzzle? - Gaul, Lewis; Uysal, Pinar (Review of Financial Studies, 2013)
[This paper examines whether unobservable differences in firm volatility are responsible for the global loan pricing puzzle, which is the observation that corporate loan interest rates appear to be lower in Europe than in the United States. We analyze whether equity volatility, an error prone measure of firm volatility, can explain this difference in loan spreads. We show that using equity volatility in OLS regressions will result in biased and inconsistent estimates of the difference in U.S. and European loan spreads. We use instrumental variable methods to identify consistent estimates and find no difference in U.S. and European loan spreads.]